Analisis Kepuasan Pengguna Alumni S3 Komunikasi Dan Penyiaran Islam Fakultas Dakwah Dan Komunikasi Universitas Islam Negeri Sumatera Utara - Khatibah Khatibah; Ahmad Tamrin Sikumbang (Journal on Education, 2023)
This study aims to determine the traces of alumni activities, in the use of knowledge obtained from universities where they study. Tracer Study research to support the improvement of the quality of human resources that will be produced. However, the problem is how the competencies possessed by alumni of the S3 KPI Doctoral Program, Faculty of Da'wah and Communication, State Islamic University of North Sumatra Medan. This research uses descriptive qualitative methods, conducts data collection through interviews and dissemination of surveys through links on google dirve. informants in this study, adjusted to the needs of the required data data. The analysis is carried out continuously and continuously from the beginning until the research is complete. The results showed that alumni user satisfaction on graduate expertise based on their scientific fields, foreign language skills, The use of information technology, communication, cooperation, and self-development of alumni is very good.